2017
DOI: 10.1111/jomf.12451
|View full text |Cite
|
Sign up to set email alerts
|

Does Parenthood Change Implicit Gender‐Role Stereotypes and Behaviors?

Abstract: This study examined whether parenthood changes gender-role behavior and implicit gender-role stereotypes as assessed with an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 60 publications
5
50
0
2
Order By: Relevance
“…Previous research has also shown that work-family conflict may depend on the parents’ gender. With the increase in the number of dual-earner families over time and the fact that parents have more traditional implicit gender-role stereotypes (i.e., women’s role as homemaker and men’s role as economic provider) than non-parents (Endendijk et al, 2018), the work-family conflict has been an issue for both parents. However, mixed results with regard to gender differences have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also shown that work-family conflict may depend on the parents’ gender. With the increase in the number of dual-earner families over time and the fact that parents have more traditional implicit gender-role stereotypes (i.e., women’s role as homemaker and men’s role as economic provider) than non-parents (Endendijk et al, 2018), the work-family conflict has been an issue for both parents. However, mixed results with regard to gender differences have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…heterosexual couples remain highly gendered with men still working most of the paid hours and women still taking on the majority of household and caregiving tasks (Craig & Mullan, 2010;European Commission, 2018;Pew Research Center, 2019). Such gendered divisions appear to develop and/or magnify after the first child is born (Endendijk et al, 2018;Grunow et al, 2012) Although such gendered tasks distributions occur across Europein comparison to men, women are employed less, work more often part-time, and do more unpaid care taskssignificant country differences can be observed (European Commission, 2018). For example, in 2018 the difference between the employment rates of men and women in Sweden was only 3.8%, but 11% in The Netherlands, 14% in Hungary and even 27.7% in Malta (European Commission, 2018).…”
mentioning
confidence: 99%
“…One way to promote equal levels of guilt in fathers and mothers may be to change parents' implicit associations and thus take away the gendered aspect of feeling guilty. Although implicit associations may not be easily malleable, a recent longitudinal study among parents of young children suggested that implicit gender associations may change as a function of personal experiences (Endendijk, Derks, & Mesman, 2018). Specifically, during the first years of parenthood, parents developed not only more traditional behaviors but also more traditional implicit gender stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In similar vein, in most families, fathers earn most of the family income (Pew Research Center, 2017). These gendered work-family distributions even magnify after men and women become parents (Endendijk, Derks, & Mesman, 2018;Grunow, Schulz, & Blossfeld, 2012).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation